__Answer with Explanation:__**Since the number is greater than the number obtained on reversing the digits, so the ten's digit is greater than the unit's digit.**

Let ten's and unit's digits be 2x and x respectively.

Then, (10 x 2x + x) - (10x + 2x) = 36

=> 9x = 36

=> x = 4.

Therefore, Required difference = (2x + x) - (2x - x) = 2x = 8.

Let ten's and unit's digits be 2x and x respectively.

Then, (10 x 2x + x) - (10x + 2x) = 36

=> 9x = 36

=> x = 4.

Therefore, Required difference = (2x + x) - (2x - x) = 2x = 8.